2011
DOI: 10.1017/s1368980011000498
|View full text |Cite
|
Sign up to set email alerts
|

Access to food source and food source use are associated with healthy and unhealthy food-purchasing behaviours among low-income African-American adults in Baltimore City

Abstract: Objective: Although previous research has shown limited availability of healthy food in low-income urban neighbourhoods, the association between food source use and food-purchasing patterns has not yet been examined. We explored foodpurchasing patterns in the context of food source use and food source access factors in low-income areas of Baltimore City. Design: Cross-sectional survey. Setting: Predominantly low-income neighbourhoods in East and West Baltimore City. Subjects: A total of 175 low-income African-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 35 publications
5
114
4
3
Order By: Relevance
“…Traveling and finances have been shown to discourage low-income families from adopting healthier lifestyle habits and behaviors (D'Angelo, Suratkar, Song, Stauffer, & Gittelsohn, 2011;Webber, Sobal, & Dollahite, 2010). Although the current study did not identify life situations that might hinder participant's selection of healthy foods, the results do indicate that participants' confidence to select healthy foods and to use the NFP increased.…”
Section: Rq #1: Intervention's Impact On Confidencecontrasting
confidence: 72%
See 1 more Smart Citation
“…Traveling and finances have been shown to discourage low-income families from adopting healthier lifestyle habits and behaviors (D'Angelo, Suratkar, Song, Stauffer, & Gittelsohn, 2011;Webber, Sobal, & Dollahite, 2010). Although the current study did not identify life situations that might hinder participant's selection of healthy foods, the results do indicate that participants' confidence to select healthy foods and to use the NFP increased.…”
Section: Rq #1: Intervention's Impact On Confidencecontrasting
confidence: 72%
“…D'Angelo et al (2011) recruited participants from an area of Baltimore with limited access to supermarkets and limited availability to healthy food options. These researchers found that unhealthy foods were more likely to be selected from grocery store shelves when these low income families had to walk to the grocery store (D'Angelo, et al, 2011). Participants from the current study were observed utilizing the Delaware County's bus services or walking to the intervention sites, possibly increasing the difficulty of obtaining healthy foods when grocery shopping.…”
Section: Rq#2: Intervention's Impact On Knowledgementioning
confidence: 87%
“…Food deserts are not unique to the USA, but the literature for the American food system is most abundant (Beaulac et al 2009). Much research has documented the lack of access to supermarkets, racial/ethnic and socioeconomic disparities in food access, differences in chain versus non-chain stores, cost of food, availability of particular food items, and links to obesity (Franco et al 2008;Larson et al 2009;Schafft et al 2009;Walker et al 2010;D'Angelo et al 2011). The findings point to a trend of low-income and ethnic minority neighborhoods in the USA facing more barriers to accessing healthy and affordable food (Walker et al 2010).…”
Section: Three Scales Of Urban Agriculturementioning
confidence: 99%
“…1 The setting for the implementation and evaluation of this nutrition education program was Baltimore, Maryland, a city rife with socioeconomic hurdles and a preponderance of ''food deserts'' in which access to healthy foods is limited. 20 Community stakeholder engagement with parents, students, and school faculty revealed that experiential nutrition education featuring cooking skills and an emphasis on flavorful foods that students enjoy would help promote sustainable dietary improvements in our target population.…”
Section: Introductionmentioning
confidence: 99%